IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS AKHLAK KEMANDIRIAN - Rianawati, Rianawati (Universitas Islam Negeri Raden Intan Lampung, 2014)
THEIMPLEMENTATIONOFMORALSANDINDEPENDENCE- BASED CONTEXTUAL LEARNING MODELS (Class Action Research on Moral Subjects in MAN 1 Pontianak): This study explores the implementation of contextual learning in order to improve student’s learning independence. The study was conducted in MAN I Pontianak using analytical models of Miles and Huerman. The study concludes that : (1) the process of learning using traditional methods tends to generate negative output marked with : (a) students are not accustomed to think analytically, (b) unable to give an opinion, (c) do not focus on learning, and (4) have a low absorption level; (2) On the contrary, through contextual learning methods, students are able : (a) to design and to build their knowledge, (b) to conduct a question and answer with a critical, systematic, analytical and logical; to be able to solve the problem together, (c) to check the results of learning, and to apply the knowledge gained. (3) Contextual learning model proves to be effective in improving student learning independence.